Carriage of Campylobacter spp. and Salmonella spp. by house flies - Choo, Li Chen; Abdul Aziz, Saleha (2010)
Sixty samples consisting of three house flies in each, were collected around a large animal ward of University Veterinary Hospital (UVH) UPM, a cafeteria and a poultry farm. Twenty samples were collected from each site. The external surface and internal content of each sample were examined for Campylobacter spp. and Salmonella spp. All samples were cultured for Campylobacter spp. via direct plating on CCDA. Three samples (2.5%) were positive for Campylobacter spp. Pre-enrichment, enrichment and direct plating on XLT4 agar were done for isolation of Salmonella spp. from the house flies. Ten samples were positive for Salmonella spp. Isolation of Salmonella spp. from all three sites suggested that the areas were contaminated with Salmonella spp. It is possible that the flies could have picked Salmonella spp. from other places around the campus. This study showed that house flies could carry both Campylobacter spp. and Salmonella spp. internally and externally. The flies could readily contaminate the environment with their droppings or come in direct contact with food or feed. It is advisable that the population of house flies must be controlled by proper manure management, sanitation and clean lifestyle.